Mimetic accuracy and co-evolution of mimetic traits in ant-mimicking species - Pekár, Stano; Martišová, Martina; Špalek Tóthová, Andrea; Haddad, Charles R (iScience, 2022)
Myrmecomorphy is the most frequent type of Batesian mimicry. Myrmecomorphic species differ in the accuracy with which they resemble ants; however, the hypothesis of the co-evolution of mimetic traits has been rarely tested. Here, we measured dozens of traits of color, shape, size, and behavior, and quantified objectively the resemblance between dozens of arthropod mimics and ants. In all traits, the mimics were more similar to ants than to closely related non-myrmecomorphic species. We found that mimics resemble ants mainly in color and behavior, and less in size and body shape. We found that the mimetic accuracy in four trait categories demonstrate divergent co-evolutionary patterns. Mimetic accuracy in color was positively correlated with shape and size in insects but negatively in spiders, presumably reflecting developmental constraints. Accuracy in shape tend to be negatively related to movement in both insects and spiders supporting the motion-limited discrimination hypothesis.
Keywords: Biological sciences; Phylogenetics; Evolutionary biology